Shear resistance and post-buckling behavior of corrugated panels in steel plate shear walls. (October 2018) - Dou, Chao; Pi, Yong-Lin; Gao, Wei
Abstract: Steel corrugated shear wall (SCSW) is an alternative to traditional shear walls with flat plates. However, shear resistance behavior and design of the infilled corrugated panels in SCSWs has not been well studies. This paper focuses on the shear resistance of sinusoidally corrugated panels in SCSWs under monotonic lateral shear force, via finite element analyses (FEA) considering both geometric nonlinearity and material elasto-plasticity. Firstly the effects of initial imperfections and geometric dimensions on shear resistance of corrugated panels are explored. Then based on extensive FEA, the maximum and the post-buckling strengths are investigated, and fitting equations to predict the shear resistant behavior of corrugated panels are proposed by introducing the normalized height-to-thickness ratio. It is found that, the maximum shear resistance of corrugated panels has a consistent relationship to the normalized height-to-thickness ratio, however variation of the post-buckling resistance is complex and geometric parameters have to be properly chosen to avoid significant strength drop after buckling. The equations proposed agree with the FEA results, and can be utilized in design of corrugated panels in SCSWs. Highlights: Corrugated panels under shear are sensitive to geometric imperfections. Equations for the maximum shear resistance for corrugated panels are proposed. Equations for residual resistances are for good post-buckling behavior. Load-displacement curves of corrugated panels under shear can be predicted.